The Implementation of Development of School Culture-Based Religious Education - Kurnali Sobandi (Ta'dib: Jurnal Pendidikan Islam, 2016)
In general, religion and religious education serve to create the Indonesian human faith and the obedience to God Almighty, also to create noble, and capable people in maintaining the harmony of inter-religious relations. In addition it serves to cultivate the participants' ability to understand, appreciate and practice the values of religion are offset mastery in science, technology and art. The development of school culture based religious education in public schools is an alternative solution on the problems which are actually classic, but until now they have not been resolved properly, which in turn would be a matter of continuity up from one period to the next, namely the problem of narrow time allocation, three hours for elementary, 2 hours face to face for SMP and SMA / SMK (per-hour 40 minutes instead of 60 minutes) and the problems therein multicultural religious plurality. Implementation of the development of school-culture based religious education in public schools covers the principles of development, through a learning process, learning outcomes assessment, and indicators of school and classroom assessment.Secara umum, agama dan pendidikan agama mencetak  manusia Indonesia menjadi  beriman, patuh pada Tuhan, juga berakhlak mulia, sehingga mampu mempertahankan hubungan antar umat beragama yang harmonis. Selain itu, pendidikan agama juga berfungsi untuk menumbuhkan kemampuan peserta didik untuk memaahami, menghargai dan mempraktikkan nilai-nilai agama dalam ilmu pengetahuan, teknologi serta seni. Pengembangan pendidikan agama berbasis school culture di sekolah umum adalah solusi alternatif atas problematika yang sebenarnya bersifat klasik, namun hingga kini belum juga terselesaikan dengan baik, sehingga pada gilirannya akan menjadi persoalan yang berkesinambungan hingga dari satu periode ke periode berikutnya yaitu problematika alokasi waktu yang sempit yakni tiga jam untuk SD, 2 jam tatap muka untuk SMP dan SMA/SMK (per-jam bukan 60 menit tetapi 40 menit) dan problematika multikultural didalamnya pluralitas agama. Implementasi pengembangan pendidikan agama berbasis school culture di sekolah umum memuat prinsip pengembangan, melalui proses pembelajaran, penilaian hasil belajar, dan indikator penilaian sekolah dan kelas.